Chance of Local Independence in Hungary - Pálné Kovács, Ilona (Discussion Papers, 1988)
The paper accompanies the process which led to the model change of local governance in Hungary in 1990. The author tries to introduce the elements, phases of local/territorial public administration, the so called soviet council system which determined the chances of autonomy of local actors before the systemic change. The soviet type of local administration based on party sate model stemming from the Soviet Constitution passed in 1936 which did not allow any local discretion since municipalities and counties were subordinated the upper level governments. Based on own empirical researches the author describes the local political scene in three smaller Hungarian settlements (Pécsvárad, Jakabszállás, Kiskunmajsa). The empirical experiences proved that local politicians and the civil society had no chance to represent their interests due to the monolithic logic of public power of state socialism. There were, however, some signs of civicness and power technics of local elite which could be seen as promising bases of approaching systemic change in local governance. Looking at the results of local community studies conducted in USA and Western Europe in the seventies the Hungarian case showed that not just the political, social-economic system but the specific features, traditions of the given country also matter as regards the chance of local autonomy.